Atkins' physical chemistry - Atkins, Peter; de Paula, Julio (New York : Oxford University Press, 2010)
This volume features a greater emphasis on the molecular view of physical chemistry and a move away from classical thermodynamics. It offers greater explanation and support in mathematics which remains an intrinsic part of physical chemistry.
Fundamentals; PART 1. EQUILIBRIUM; 1. The properties of gases; 2. The first law; 3. The second law; 4. Physical transformations of pure substances; 5. Simple mixtures; 6. Chemical equilibrium; PART 2. STRUCTURE; 7. Quantum theory: introduction and principles; 8. Quantum theory: techniques and applications; 9. Atomic structure and atomic spectra; 10. Molecular structure; 11. Molecular symmetry; 12. Molecular spectroscopy 1: rotational and vibrational spectra; 13. Molecular spectroscopy 2: electronic transitions; 14. Molecular spectroscopy 3: magnetic resonance; 15. Statistical thermodynamics 1: the concepts; 16. Statistical thermodynamics 2: applications; 17. Molecular interactions; 18. Materials 1: soft matter; 19. Materials 2: solids; PART 3. CHANGE; 20. Molecules in motion; 21. The rates of chemical reactions; 22. Reaction dynamics; 23. Catalysis; Resource section
Includes bibliographical references and index.
Keywords: CHEMISTRY, PHYSICAL AND THEORETICAL -- TEXTBOOKS